2004
DOI: 10.1002/14651858.cd000058.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine for smoking cessation

Abstract: Transdermal Nicotine Study Group. Transdermal nicotine for smoking cessation. Six-month results from two multicenter controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
13

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 28 publications
1
90
0
13
Order By: Relevance
“…Forty-one systematic reviews were identified, of which 12 focused on pharmacotherapies for smoking cessation. [138][139][140][144][145][146][147][148][149][150][151][152] The 12 systematic reviews were screened to identify studies that assessed specific pharmacotherapies with evidence of effectiveness. The full texts of the papers identified from the included Cochrane reviews were then screened independently by two authors (JL-B and SA or AMcN and TC) using a specially designed data extraction form to assess whether they fulfilled the pre-specified inclusion criteria (see Box 7, Figure 16).…”
Section: Process For Identifying Studiesmentioning
confidence: 99%
“…Forty-one systematic reviews were identified, of which 12 focused on pharmacotherapies for smoking cessation. [138][139][140][144][145][146][147][148][149][150][151][152] The 12 systematic reviews were screened to identify studies that assessed specific pharmacotherapies with evidence of effectiveness. The full texts of the papers identified from the included Cochrane reviews were then screened independently by two authors (JL-B and SA or AMcN and TC) using a specially designed data extraction form to assess whether they fulfilled the pre-specified inclusion criteria (see Box 7, Figure 16).…”
Section: Process For Identifying Studiesmentioning
confidence: 99%
“…Meta-analyses (table 1) indicate that various pharmacological treatments improve SC: nicotine replacement therapy, substitutes of nicotine [64,65,66,67,68,69], bupropion and nortriptyline (antidepressants) [67,70,71,72,73,74], and varenicline, cytisine and mecamylamine (agonists of the nicotine acetylcholine receptors) [67,75,76,77,78]. Naltrexone, an opioid antagonist, has no significant impact on SC [79].…”
Section: Resultsmentioning
confidence: 99%
“…Vareniklin dapat menyebabkan gejala gastrointestinal (mual, konstipasi, dispepsia, muntah), sakit kepala, insomnia, mimpi buruk [11]. Klonidin dapat menyebabkan mulut kering dan sedasi [12]. Faktor biaya juga merupakan masalah yang dapat ditimbulkan pada proses terapi obat untuk pemberhentian merokok.…”
Section: Pendahuluanunclassified